Hydration kinetics and performance of sodium carbonate-activated slag-based systems containing reactive MgO and metakaolin under carbonation - Akturk, Busra; Abolfathi, Mehrnosh; Ulukaya, Serhan; Kizilkanat, Ahmet B.; Hooper, Thomas J. N.; Gu, Lei; Yang, En-Hua; Unluer, Cise (ELSEVIER SCI LTD, 2022)
The hydration mechanism and strength development of sodium carbonate-activated slag-based systems mainly depend on the additives used. Although the effects of mineral additives in such systems have been extensively investigated, the effects of Mg2+, Al3+, and Si4+ ions increasing with the addition of reactive MgO (Mg) and metakaolin (Mk) on the hydration mechanism of such systems have not been established yet. This study investigated the hydration kinetics and performance of sodium carbonate-activated ternary blended slag-based binder systems. The hydration mechanism was revealed by isothermal calorimetry and mechanical performance was evaluated with the measurement of compressive strength at different ages up to 56 days. The reaction mechanisms were investigated through X-ray diffraction, Fourier transform infrared spectroscopy, thermogravimetric analysis and 29Si and 27Al solid-state nuclear magnetic resonance (NMR). C-(A)-S-H, Na and Al-enriched C-(N,A)-S-H and hydrotalcite were the main reaction products responsible for the strength development of the samples, accompanied by the minor contribution of other carbonate-containing phases. Partial replacement of slag with Mg and Mk led to high early-age strengths compared to plain samples when Mk was used at 5%. Samples incorporating Mg and Mk achieved similar or higher strengths than ordinary Portland cement-based samples. However, an increase in replacement ratio of Mk beyond 5% led to a significant decrease in compressive strength. Furthermore, the performance of samples under accelerated carbonation was studied. The use of Mg and Mk enhanced carbonation resistance due to enhanced hydrotalcite and C-(N,A)-S-H gel formation, highlighting the potential of using slag-Mg-Mk blends as an alternative binder system.
Keywords: Sodium carbonate activation; Reactive MgO; Metakaolin; Slag; Microstructure; Accelerated carbonation; CALCIUM SILICATE HYDRATE; C-S-H; FLY-ASH; ALKALINE ACTIVATION; CHEMICAL-SHIFTS; WASTE GLASS; PART I; STRENGTH; NMR; CONCRETE; Construction & Building Technology; Materials Science